Long‐term in vivo assessment of bioengineered skin substitutes: a clinical study. (24th June 2014) - Nicoletti, Giovanni; Brenta, Federica; Bleve, Mariella; Pellegatta, Tommaso; Malovini, Alberto; Faga, Angela; Perugini, Paola
Abstract The aim of the study was an objective in vivo assessment of skin properties after reconstruction with two artificial dermal substitutes, Integra® and Hyalomatrix®. Twenty‐seven patients underwent reconstruction of 36 skin‐loss sites with full‐thickness skin graft, split‐thickness skin graft, Hyalomatrix® bioengineered skin substitute and sequential split‐thickness skin graft and Integra® bioengineered skin substitute and sequential split‐thickness skin graft. Objective assessments were carried out using three instrumental devices: Multi Probe Adapter System MPA; 22 MHz ultrasound skin scan; and Primos Pico for a three‐dimensional (3D) skin scan. The skin parameters under study in our sample were: corneometry, transepidermal water loss, elastometry, colorimetry, skin thickness and 3D skin surface pattern. A skin reconstruction with Hyalomatrix seemed to most closely approach the hydration, transepidermal water loss and skin surface 3D pattern of normal skin. A skin reconstruction with Integra seemed to demonstrate the best skin colour feature and elastic properties. Although no statistically significant differences were observed, the descriptive analysis of the outcomes might suggest a better cell regulation, regenerated extracellular matrix and neoangiogenesis with the use of Hyalomatrix, and the formation of a more elastic regenerated dermis, with overall better physical, mechanical and optical properties, with the use of Integra. © 2014 The Authors. Journal of Tissue Engineering and Regenerative Medicine published by John Wiley & Sons Ltd.